Qualidade da água e conflitos socioambientais do submédio e baixo São Francisco - Santos, Dayanara Mendonça (2022)
The relationship of man with nature was established under the aegis of simplification and domination of natural elements, resulting in complex environmental problems, the possible solutions demand multidisciplinary dialogues for understanding and structuring sustainable solutions. The dissertation aimed to understand the environmental dynamics associated with water quality and its impacts on the São Francisco River basin. Two research methods were used, the hypothetical-deductive of Popper (1975) and the Complex method of Morin (1977) applied to the analysis of environmental conflicts. The spatial scope of the research was the region of the lower and middle São Francisco. For the land use and land cover analysis we used the software Qgis and data from MapBiomas, as for water quality, it was obtained through the principal components analysis (PCA). The conflicts were analyzed based on Luhmann (2006). The results obtained indicate that there was a reduction in natural forest and non-vegetated areas and an increase in other uses between the years 2016 and 2020, especially in the São Francisco sub-medium. There were significant differences between 2016 and 2021 mainly in the lower course region, the main source point of the variations is located in the municipality of Piaçabuçu, followed by the points positioned in Canindé de São Francisco and Paulo AfonsoBA, the elements that presented the greatest source of variation were nitrate (NO3) total nitrogen (N), electrical conductivity (EC) and Dissolved Oxygen (DO), with significant reductions within the time frame. As for conflicts, there was an increase in the number of conflicts between the years 2016 and 2020, with a peak in 2019, being the states of Sergipe and Alagoas the main ones in the filing of lawsuits, having as social actors fishermen, state and businessmen, reflecting the demand for integration in the knowledge produced and define the necessary elements in decision making. The research concludes that the lower and lower São Francisco are constantly undergoing changes in the dynamics of land cover, with an increase in agricultural and aquaculture production, changes in water quality do not always occur at the place where the damage is generated, and the lower course is the one that suffers more impacts from anthropic and natural actions, which requires complex actions and a complete view of the environment analyzed.